HOMONIM DAN POLISEMI BAHASA JERMAN PADA PUISI-PUISI KARYA CHRISTIAN MORGENSTERN - Yona Zezillia Valentine; Agus Ridwan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Semantic relations in literary works play a crucial role in shaping the meaning of polysemous words, which function not only semantically but also aesthetically and rhetorically. One poet renowned for rich wordplay is Christian Morgenstern, whose poems employ humor, irony, and absurdity through the use of homonymy and polysemy. This study aims to describe semantic relations involving homonymy and polysemy based on their semantic features. Using a qualitative descriptive approach grounded in Geoffrey Leech’s semantic theory, the findings reveal that homonymy in Morgenstern’s poetry manifests in words whose meanings are contextually interrelated. From a semantic perspective, polysemy represents the extension of related meanings, allowing a single lexical item to generate multiple interpretations. These phenomena not only highlight the lexical richness of the German language but also produce layered aesthetic and rhetorical effects. Thus, semantic analysis of homonymy and polysemy reveals the complex structures of meaning embedded in Christian Morgenstern’s poetry